(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
And this belief is the one that God sent His Messengers with and revealed His books and made obligatory upon all His creation, make them human and make them crazy. Evidence is the decisive guide inIslamic belief, just as the evidence is a guide inareas of contention, dispute and quarrels; The basic principle is that after the evidence it is not permissible to quarrel, dispute or disagree, and the judge waits in his judgment until the plaintiff comes with evidence and judges it while he is confident in it, and without it, disputes remain, and disputes continue, and since the Islamic belief is one of the most important matters that is not proven in a person’s belief except with evidence. decisive, for it is from the mercy of God - the Most High - that he did not leave the matter of its stability in the souls to the mind that infers it with cosmic evidence only. Rather, God - Glory be to Him - sent messengers who recite His books and revealed books as a revelation to the unbelievers from the People of the Book and the polytheists until they stop their delusions; For had it not been for God’s sending of the Messengers and the revelation of the Books, it would not have ended, and the infidels would not have abandoned their unbelief.)Those who disbelieved among the People of the Book and the polytheists were not disbelieving until clear evidence came to them